Light-addressable electrochemistry at semiconductor electrodes: Redox imaging, mask-free lithography and spatially resolved chemical and biological sensing - Vogel, Yan; Gooding, J.J.; Ciampi, Simone (ROYAL SOC CHEMISTRY, 2019)
© 2019 The Royal Society of Chemistry.